Selected meat quality parameters and nutritional profiles of M. longissimus thoracis et lumborum of Niang-Megha pigs - THOMAS, R; BANIK, S; BARMAN, K; MOHAN, N H; SARMA, D K (The Indian Journal of Animal Sciences, 2018)
Niang Megha is one of the 7 registered pig breeds of indigenous origin in India. The study was part of a programme to improve pig production in India and the information on carcass composition and meat quality are very much essential towards the development of a suitable breeding plan for this pig breed. Gilts (14) and barrows (20) from Niang Megha breed were slaughtered at the age of 10 months for evaluating the different parameters. Moisture: protein ratio varied from 3.38 to 3.64 and no significant difference was observed between gilts and barrows. The cholesterol content in M. longissimus thoracis et lumborum varied from 46.81 mg/100g to 68.15 mg/ 100g, with an average of 60.68 mg/100g. Instrumental colour measurement indicated that the coordinates were in the following range: lightness (L*), 55.83–74.18; redness (a*, red±green), 9.81–19.37; and yellowness (b*, yellow±blue), 19.97–39.38. The haem iron content was significantly higher in barrows compared to gilts. The mineral contents in the M. longissimus thoracis et lumborum were in the following range: potassium, 271–337 mg/ 100g; zinc, 0.54–0.97 mg/100g; copper, 0.03–0.09 mg/100g; manganese, 0.02–0.03 mg/100g, and magnesium, 4.37–7.22 mg/100g. Significant differences were not observed in the concentration of any of the estimated amino acids between the sexes. Fatty acid profiling of M. longissimus thoracis et lumborum indicated that saturated and unsaturated fatty acids were in the range of 32.75%–38.91% and 54.69%–69.28%, respectively.